Who was Sacagawea? (Who was-- ?, , 1, 2002)
Sacagawea was only sixteen when she made one of the most remarkable journeys in American history, traveling 4500 miles by foot, canoe, and horse-all while carrying a baby on her back! Without her, the Lewis and Clark expedition might have failed. Through this engaging book, kids will understand the reasons that today, 200 years later, she is still remembered and immortalized on a golden dollar coin.

Who was Albert Einstein? (Who was-- ?, , 1, 2002)
Everyone has heard of Albert Einstein-but what exactly did he do? How much do kids really know about Albert Einstein besides the funny hair and genius label? For instance, do they know that he was expelled from school as a kid? Finally, here's the story of Albert Einstein's life, told in a fun, engaging way that clearly explores the world he lived in and changed.
Born to Think , What's to Be Done with a Genius? , Albert Takes a Very Deep Breath ... and Keeps Thinking , The Best Years , Albert Hits High Gear , War ... Again , Albert's Time Is Up.